Drivers of global liquidity and global bank flows: A view from the euro area - Mary Everett (FIW - Research Centre International Economics, 2016)
This paper exploits a novel bank-level monthly dataset to assess the effects of global liquidity on the global flows of euro area banks. The period associated with the European sovereign debt crisis has witnessed increased growth in euro area bank claims on extra-euro area residents, against a background of contracting euro area credit supply. Controlling for bank risk, global credit demand, and price effects such as interest rate differentials and exchange rates, empirical evidence supports a range of determinants of global liquidity - including global risk, global bank equity and unconventional monetary policy in the US, UK, Japan and euro area - as drivers of the global flows of euro area banks. Moreover, regression analysis indicates heterogeneity in the influence of global liquidity on global flows across euro area bank type, defined by their balance sheet composition and country of residence (stressed versus non-stressed euro area countries). The results highlight the importance of exogenous factors as drivers of global bank flows and the potential for international leakages of unconventional monetary policy.
Keywords: F60; G15; G21; 330; global bank flows; cross-border banking; global risk; global liquidity; European sovereign crisis; unconventional monetary policy spillovers; credit supply